1972
DOI: 10.1159/000252042
|View full text |Cite
|
Sign up to set email alerts
|

Trimethoprim-Sulphamethoxazole in Acne vulgaris A Double-Blind Study

Abstract: A double-blind cross-over trial of the effect of trimethoprim-sulphamethoxazole (Bactrim® Roche) and placebo was carried out on 43 patients with. The dose of trimethoprim-sulpha- Acne vulgaris methoxazole was 80 and 400 mg, respectively, (1 tablet) daily. The active preparation and the placebo were given for 5 weeks. After this time the group initially given the active preparation was given the placebo and vice versa. Acne lesions were classified in various degrees of severity and counted according to a method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…We identified 48 clinical trials investigating systemic tetracycline treatment efficacy in inflammatory acne, 11–58 29 trials investigating minocycline systemic treatment efficacy, 28,37,39,45,46,54,58–80 10 trials investigating doxycycline systemic treatment efficacy 8,9,20,62,68,69,81–84 and seven trials investigating lymecycline systemic treatment efficacy, 77,80,85–89 57 of which were included 8,9,12,14,16,17,19–21,23,25–38,41,42,44–52,54,56–58,62,66,69,71,72,75–81,83–88 . Trials were excluded for the following reasons: combination with other topical or systemic drug with antiacne efficacy, 18,53,55,64,68,73,74,82,89 use of obsolete drugs, 11,15,22 antibiotic treatment < 1 month prior to the study or selection of cases unresponsive to other antibiotics, 24,53,59,61,63,67,74 duplicate reports, 70 specific forms of acne (nodulocystic acne, 43,65 oil acne 40 ), cross‐over studies 13,18,39,60,63 …”
Section: Resultsmentioning
confidence: 99%
“…We identified 48 clinical trials investigating systemic tetracycline treatment efficacy in inflammatory acne, 11–58 29 trials investigating minocycline systemic treatment efficacy, 28,37,39,45,46,54,58–80 10 trials investigating doxycycline systemic treatment efficacy 8,9,20,62,68,69,81–84 and seven trials investigating lymecycline systemic treatment efficacy, 77,80,85–89 57 of which were included 8,9,12,14,16,17,19–21,23,25–38,41,42,44–52,54,56–58,62,66,69,71,72,75–81,83–88 . Trials were excluded for the following reasons: combination with other topical or systemic drug with antiacne efficacy, 18,53,55,64,68,73,74,82,89 use of obsolete drugs, 11,15,22 antibiotic treatment < 1 month prior to the study or selection of cases unresponsive to other antibiotics, 24,53,59,61,63,67,74 duplicate reports, 70 specific forms of acne (nodulocystic acne, 43,65 oil acne 40 ), cross‐over studies 13,18,39,60,63 …”
Section: Resultsmentioning
confidence: 99%
“…Vaginal candidiasis may complicate the use of all oral antibiotics. 102,103,107,108 Doxycycline can be associated with photosensitivity. Minocycline has been associated with pigment deposition in the skin, mucous membranes and teeth particularly among patients receiving long-term therapy and/or higher doses of the medication.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials of treatment of acne vulgaris with minocycline in doses of 100 mg daily have demonstrated a statistically significant decrease in lesion count when compared with placebo. 46 Still, no statistically significant differences have been demonstrated in clinical trials when comparing minocycline with doxycycline, and investigators have concluded that both are equally effective in the treatment of moderate to moderately severe acne vulgaris. [47][48][49] An extended-release (ER) version of minocycline tablets at a dosage of 1 mg/kg/day (Solodyn ® ; Medicis Pharmaceutical Corporation) was approved in 2006 for the treatment of moderate-to-severe acne in patients older than 12.…”
Section: Doxycycline Versus Minocyclinementioning
confidence: 99%